Correction: Silk fibroin–keratin based 3D scaffolds as a dermal substitute for skin tissue engineering. Issue 1 (1st December 2014) - Bhardwaj, Nandana; Sow, Wan Ting; Devi, Dipali; Ng, Kee Woei; Mandal, Biman B.; Cho, Nam-Joon
Abstract : Correction for 'Silk fibroin–keratin based 3D scaffolds as a dermal substitute for skin tissue engineering' by Nandana Bhardwaj et al., Integr. Biol., 2015, DOI: 10.1039/c4ib00208c.